Quantum computation with photochromic films in a Mach–Zehnder interferometer - Scotognella, Francesco (Frontiers in Nanotechnology, 2024)
Photochromic materials are of great interest because they enable the fabrication of photo-activated switches. In this study, an experiment is proposed in which two chromene-based photochromic layers were inserted into the arms of a Mach-Zehnder interferometer. Chromene was studied from the perspective of optical absorption to determine the wavelength-dependent complex refractive index. Impinging ultraviolet light on one of the chromene layers induces a transition from the closed to the open form of the chromene, resulting in different phase shifts in the two arms of the interferometer. This results in a change in the probability of detecting a photon by the two detectors after the second mirror of the Mach-Zehnder interferometer. The experiment may have some interest in the fields of quantum information and quantum communications.